The effects of leadership style on employee well-being in hospitality - Kara, D.; Uysal, Muzaffer; Sirgy, M.; Lee, G. (Pergamon, 2013)
We conducted a study to test the notion that transformational leadership style is more effective than transactional leadership style by fostering employee well-being (enhancing quality of work life and life satisfaction as well as increasing organizational commitment and decreasing employee burnout. We surveyed 443 employees at 5-star hotels in Turkey. The results provide support for the positive effect of transformational leadership in the hospitality industry, which implies that hospitality managers should be trained to use a transformational leadership style to enhance employee well-being.